2018
DOI: 10.1037/xap0000163
|View full text |Cite
|
Sign up to set email alerts
|

Display of major risk categories for android apps.

Abstract: Communicating cybersecurity risks to mobile-device users is essential. However, existing means of conveying the risks through detailed permission lists are ineffective. Risk indexes that convey overall risk are effective at influencing app-selection decisions, but many users want more information. We examined how users assess the risks associated with downloading applications on the Android platform by comparing various graphical formats of intermediate-level risk displays containing three risk categories: per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 62 publications
3
13
0
Order By: Relevance
“…People also increasingly use screens and computer aided display in areas like healthcare (Kunar et al, 2017), geo-location (Hegarty et al, 2016), driving (Rizzardo et al, 2013), and learning (Johnson & Mayer, 2012). The proliferation of smartphones has made it easier to access numerical information at any time and any place (Chen et al, 2018), and simulations have made it possible to use complex data for estimations (Brunyé et al, 2014). In these technology-enriched contexts, people receive estimates in both point value and interval form (Padilla et al, 2015), and later compare estimates to observed values.…”
Section: Comparing Estimates For Decision-makingmentioning
confidence: 99%
“…People also increasingly use screens and computer aided display in areas like healthcare (Kunar et al, 2017), geo-location (Hegarty et al, 2016), driving (Rizzardo et al, 2013), and learning (Johnson & Mayer, 2012). The proliferation of smartphones has made it easier to access numerical information at any time and any place (Chen et al, 2018), and simulations have made it possible to use complex data for estimations (Brunyé et al, 2014). In these technology-enriched contexts, people receive estimates in both point value and interval form (Padilla et al, 2015), and later compare estimates to observed values.…”
Section: Comparing Estimates For Decision-makingmentioning
confidence: 99%
“…A ''high risk'' display was investigated in A6 [51]. Through three online experiments, this research aimed to evaluate the effectiveness of different representations of major risk categories -the intermediate level of risk representations (personal privacy, monetary loss, and device stability) in the context of mobile app installation.…”
Section: C: Mobilementioning
confidence: 99%
“…In the context of mobile app installation, A6 [51] established that the ''low risk rating'' cue influenced application selection. The results showed that applications with lower risk ratings were more likely to be chosen for installation.…”
Section: B: Mobilementioning
confidence: 99%
“…Furthermore, Rajivan and Camp tested the effectiveness of different iconography on promoting safe decision making and found that locks resulted in the safest choices, likely due to the familiarity of the icon and associated mental models with web browsers. Alternatively, Chen et al (2018) investigated intermediate-level risk displays containing three major risk categories as opposed to the summary risk/safety ratings in the research by Chen et al (2015), Rajivan and Camp (2016), and Chong et al (2018), and found that displaying these risk categories promoted secure app selections and allowed for potential personalization of risk displays based on the user's risk concerns. Finally, a study by Shuster et al (2015) tested users' preference for risk presentation between automated reports and human reviews.…”
Section: Prior Studies On Risk Displays For Mobile Applicationsmentioning
confidence: 99%
“…Based on the ICC calculated for the current study's data, a higherorder analysis, such as HLM (Lindley & Smith, 1972) was deemed unnecessary. Rather, a generalized linear mixed-effects regression with the random intercept effects for participants and app function was used in R to analyze choice data (Baayen, 2008;Chen et al, 2018). Participants and app function served as random factors to account for variability not explained by brand familiarity, security score, time pressure, or security framing.…”
Section: Choice Datamentioning
confidence: 99%